1987
DOI: 10.1111/j.2042-3306.1987.tb02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations and management of fractures of the proximal phalanx in young Thoroughbreds

Abstract: Summary A retrospective study of 119 cases of fracture of the proximal phalanx is described. The short incomplete sagittal fracture (split pastern) was most common and carried a good prognosis for a return to racing following conservative treatment. Longer incomplete fractures also had a good prognosis but complete fractures, either through the lateral cortex of the proximal phalanx or through the bone into the proximal interphalangeal joint, required internal fixation. Careful assessment of these and comminut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 2 publications
8
59
3
Order By: Relevance
“…This result coincides with the cli-nical evidence that fracture of the trabecular region is the most common in the proximal phalanx (Nixon 2012). In this study post-fracture CT images revealed that most fracture lines were located in the sagittal plane at the proximal or distal trabecular regions, similarly to an earlier retrospective study (Ellis et al 1987). Thus, it would be important to focus on this region in further studies, as the trabecular region appears to be the key component in sagittal proximal phalanx fractures.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This result coincides with the cli-nical evidence that fracture of the trabecular region is the most common in the proximal phalanx (Nixon 2012). In this study post-fracture CT images revealed that most fracture lines were located in the sagittal plane at the proximal or distal trabecular regions, similarly to an earlier retrospective study (Ellis et al 1987). Thus, it would be important to focus on this region in further studies, as the trabecular region appears to be the key component in sagittal proximal phalanx fractures.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it would be important to focus on this region in further studies, as the trabecular region appears to be the key component in sagittal proximal phalanx fractures. Proximal phalanx fractures are categorized as sagittal or transverse, the latter extends across the bone and does not involve articular surfaces (Ellis et al 1987). Sagittal proximal phalanx fractures are categorized as incomplete or complete.…”
Section: Discussionmentioning
confidence: 99%
“…Most P1 fractures in the Thoroughbred racehorse occur in a predictable configuration, along a sagittal plane through the proximal sagittal groove (Ellis et al. ; Stover, ; Murray et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…One theory of aetiology for sagittal fractures of P1 is that the rotary movement between the sagittal groove of the proximal P1 and the distal third metacarpal bone (McIII) sagittal ridge, induces compressive and torsional forces that ultimately lead to fracture as an acute biomechanical event or monotonic overload (Markel & Richardson, ; Ellis et al. ; Holcombe et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that the decrease in the bone tissue parameters in the vicinity of proximal metaphysic of the proximal phalanx can be conducive to this type of fractures. Bone fractures are more likely to occur in the context of low bone tissue parameters such as decrease in the number of bone trabeculae, their volume, density and width [2,3]. Unfortunately, there are few reports on the bone tissue parameters of the proximal phalanges.…”
Section: Introductionmentioning
confidence: 99%